Medical simulation: an essential tool for training, diagnosis, and treatment in the 21st century - Carlos Enrique Mawyin-Muñoz; Francisco Javier Salmerón-Escobar; Javier Aquiles Hidalgo-Acosta; Maria Fernanda Calderon-León (BMC Medical Education)
Abstract Background Medical simulation is a global trend that improves disease interpretation, diagnostic skills, and clinical abilities, transforming them into skills for the practitioner. Simulator classes should be part of continuing medical education, generating advances that make it necessary for technical development and specialization in complex, complicated, or difficult-to-reproduce scenarios that students may face, based on clinical problems with negative feedback, allowing for learning from mistakes. The objective of the review is to identify the usefulness of simulation in teaching the new medicine. Methods Using the PRISMA 2020 declaration, articles published in the last 5 years on simulation teaching in neurology were reviewed. These articles were sourced from databases such as PubMed, Mendeley, Wiley, Web of Science, Cochrane, Latindex, and Google Scholar. In the summary of results, only those studies that met the inclusion criteria were selected for analysis. Results Twenty-six randomized clinical trials on medical education and training were selected. The analysis showed that simulation improved skill scores to support simulation-based medical diagnosis and treatment. Conclusion Simulation-based education has demonstrated statistical benefits in learning, skill acquisition, feedback, and stress reduction, particularly in the specialties of ophthalmology, emergency medicine, neurology, neurosurgery, neuroanatomy, and neuropathology, providing great relevance to the present review. No study reported beneficial effects or effects on mortality: despite improved surgical skill times among participants, no statistically significant data were found on a reduction in operative complications. Simulation technologies such as artificial intelligence, mixed reality, and robotics are under development, the impact of which on improving the quality of care is still unknown. Clinical trial number Not applicable.